The International Encyclopedia of Organizational Communication 2017
DOI: 10.1002/9781118955567.wbieoc044
|View full text |Cite
|
Sign up to set email alerts
|

Control

Abstract: Organizational control is broadly understood as the methods and processes used to determine what to do and how to do it in organizations. The entry presents five main types of control. Direct control is based on personal surveillance and thus concerns face‐to‐face orders from one person to another about what to do and how to do it. Technical control is when technology such as the assembly line guides the work. Under bureaucratic control, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…A feature of identity regulation, as a form of normative control, is the provision of a set of vocabulary to workers which supports the propagation of an identity narrative that encapsulates the characteristics and values that align workers with their employers’ objectives (Rennstam, 2017 ). Grab recruits its delivery riders online with slogans such as: “Partner with us to empower your livelihood and more” ; “ Take pride in satisfying millions of our hungry customers every day” ; and “Be your own boss” .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A feature of identity regulation, as a form of normative control, is the provision of a set of vocabulary to workers which supports the propagation of an identity narrative that encapsulates the characteristics and values that align workers with their employers’ objectives (Rennstam, 2017 ). Grab recruits its delivery riders online with slogans such as: “Partner with us to empower your livelihood and more” ; “ Take pride in satisfying millions of our hungry customers every day” ; and “Be your own boss” .…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have found evidence of different forms of normative control in the gig economy (Ens, 2019 ; Fleming & Sturdy, 2011 ). In our research, we focus specifically on identity regulation as a form of normative control (Rennstam, 2017 ). According to Rennstam ( 2017 ), identity regulation puts the naturally occurring socialisation process of identity formation under managerial control through measures that construct specific personal characteristics or skills as ideal characteristics of a "good" worker in the given domain.…”
Section: Literature Conceptual Framework and Methodologymentioning
confidence: 99%
See 1 more Smart Citation
“…Common concepts include clan or normative control, where control is executed through a group of like‐minded people who are motivated by commonly held values and norms (Alvesson & Willmott, 2002; Barley & Kunda, 1992; Ouchi, 1980). In informal control, colleagues and teammates are collaborators who discipline themselves and others (Coombs & Willmott, 1992), so appropriate hiring and robust socialisation processes are necessary to ensure group cohesion and discipline (Lave & Wenger, 1991; Rennstam, 2017). While informal controls generally assume a central attempt to cultivate culture, when these processes are executed diffusely, they can also unfold from the bottom up, where norms and values develop through team members (Tompkins & Cheney, 1985).…”
Section: Control On Digital Platformsmentioning
confidence: 99%